Etika Bisnis Dan Inovasi Produk Makanan Dan Minuman UMKM Di Kecamatan Semampir Surabaya - yesa cahayaning; Suhermin Suhermin; Budiyanto Budiyanto; Anang Subardjo (Universitas Lancang Kuning, 2022)
The Covid-19 pandemic has had an adverse impact on the sustainability of Indonesia's economic life, especially for Small, Micro and Medium Enterprises (MSMEs). The strategy of MSME actors in dealing with the Covid-19 pandemic situation can allegedly be done through online product marketing. Based on the identification of the previous problem, the Covid-19 pandemic has caused MSME turnover to decline. Because usually these products from MSMEs are marketed to customers at meetings organized by the surrounding community, innovation means an idea, product, information technology that can be used. MSME actors make interesting flyers about their products to be distributed to various business social media so that they can be known by a wide audience. Amondeys Cake and Adirasa Cake have tried to develop themselves through this online marketing. However, beverage SMEs still need creative efforts to produce unique and interesting products.